2005
DOI: 10.1081/ddc-52073
|View full text |Cite
|
Sign up to set email alerts
|

Oral Bioadhesive Drug Delivery Systems

Abstract: The oral mucosal cavity is a feasible, safe, and very attractive site for drug delivery with good acceptance by users. The mucosa is relatively permeable and robust, shows short recovery times after stress or damage, is tolerant to potential allergens, and has a rich blood supply. Moreover, oral mucosal drug delivery bypasses the first-pass effect and avoids presystemic elimination in the gastrointestinal tract. Bioadhesive systems provide intimate contact between a dosage form and the absorbing tissue, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(47 citation statements)
references
References 89 publications
0
44
0
3
Order By: Relevance
“…The fragile drugs can be encapsulated into polymeric nanoparticles and thus go through the GI tract. [11][12][13][14][15][16] Poly-butylcyanoacrylate (PBCA) is such a fine biodegradable polymer that has been used as surgery glue in clinic. [17][18][19][20][21][22][23] In addition, the former experiments done in our lab showed that the method to produce PBCA nanoparticles was much easier than the others.…”
Section: Introductionmentioning
confidence: 99%
“…The fragile drugs can be encapsulated into polymeric nanoparticles and thus go through the GI tract. [11][12][13][14][15][16] Poly-butylcyanoacrylate (PBCA) is such a fine biodegradable polymer that has been used as surgery glue in clinic. [17][18][19][20][21][22][23] In addition, the former experiments done in our lab showed that the method to produce PBCA nanoparticles was much easier than the others.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to obtain local and systemic effect by using mucoadhesive systems. They allow the drug to remain in the area of action for a long time, thereby providing the local effect due to increase the duration of the absorption in the absorption zone [51,52]. Mucoadhesive polymers can adhere to the surface of the gastric mucosa, thus allowing the drug to remain in this area for a longer period of time, thereby increasing bioavailability [53].…”
Section: Mucoadhesive Mini Tabletsmentioning
confidence: 99%
“…A mucosa mais utilizada para administração e absorção de fármacos é a gastrintestinal, mas outras membranas ou mucosas também têm sido estudadas, como a cutânea, nasal, ocular, bucal, vaginal, retal, oral e periodontal [10][11][12][13][14][15][16][17][18][19][20][21] . A função do muco é proteger e lubrificar o epitélio para evitar que micro-organismos e substâncias sejam absorvidos.…”
Section: Composição Estrutura E Função Do Mucounclassified